Can reducing tillage and increasing crop diversity benefit grain and forage production?. Issue 5 (11th April 2017) - Weyers, Sharon L.; Archer, David W.; Forcella, Frank; Gesch, Russ; Johnson, Jane M.F.
Abstract: Benefits of reduced tillage and diverse crop rotations include reversing soil C loss, and improving soil quality and function. However, adoption of these strategies is lagging, particularly in the Upper Midwest, due to a perception that reduced tillage lowers crop yields. Therefore, an 8-year comparison of these conservation systems with a conventional, tilled, 2-year rotation system was conducted to evaluate effects on yields, system productivity (measured with potential gross returns) and weed seed densities. This study compared conventional moldboard plow + chisel till (CT) to reduced strip-tillage + no-tillage (ST), each with a 2-year (2y) or 4-year (4y) crop rotation, abbreviated as CT-2y, CT-4y, ST-2y and ST-4y. The 2y rotation was corn ( Zea mays L.) and soybean ( Glycine max [L.] Merr.); the 4y rotation was corn, soybean, spring wheat ( Triticum aestivum L.) underseeded with alfalfa ( Medicago sativa L.) and alfalfa. Only corn grain was significantly influenced by tillage strategy; CT systems yielded more than ST systems, regardless of rotation. Soybean grain yields were similar among CT-2y, CT-4y, ST-4y and lowest in the ST-2y. Yields of wheat and alfalfa were the same under both tillage strategies. Weed seed densities were higher in wheat and alfalfa, followed by corn then soybean, but were not influenced by tillage or rotation, nor universally negatively correlated to yield. Due to greater corn yields, overall system productivity was highest in CT-2y, the same between CT-4y and ST-2y, and lowest in ST-4y. Within years, productivity of CT-2y was different from only one other system at a time in 3 of 8 years and had the same productivity as all systems in another 3 of 8 years. Additionally, the similarity of productivity among three of four systems in 6 of 8 years indicated reduced tillage and diverse rotations have potential for adoption. Results support the need for research on a rotational tillage strategy, i.e., moldboard plowing before corn, to improve overall productivity if using ST before soybean, wheat and alfalfa.